2014
DOI: 10.2478/s13531-013-0148-z
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of agricultural waste into activated carbons and its adsorption characteristics for heavy metals

Abstract: Activated carbon derived from pine cones waste was prepared by carbonization at 450 • C, activated by different activating agents: ZnCl 2 , H 2 SO 4 and NaOH, and then pyrolyzed at 600 • C. Adsorption of Cr VI and other heavy metals (Mn II, Fe II, Cu II) on activated carbons was investigated to evaluate the adsorption properties. Special attention was paid to the effects of carbon surface functionalities that were analyzed by FT-IR and zeta potential study. Moreover, XRD study of activated carbon was also carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
(35 reference statements)
1
7
0
2
Order By: Relevance
“…e entire W values are negative, becoming more negative with increasing loading or increasing initial concentration indicating that the heat of adsorption shows a decrease with loading due to repulsive interaction among adsorbed molecules. Other authors [56] also reported that the Fowler-Guggenheim model best described Cr (VI), Mn(II), Fe(II), and Cu(II) on activated carbons from agricultural wastes but with positive W values.…”
Section: (5) Elovichmentioning
confidence: 91%
“…e entire W values are negative, becoming more negative with increasing loading or increasing initial concentration indicating that the heat of adsorption shows a decrease with loading due to repulsive interaction among adsorbed molecules. Other authors [56] also reported that the Fowler-Guggenheim model best described Cr (VI), Mn(II), Fe(II), and Cu(II) on activated carbons from agricultural wastes but with positive W values.…”
Section: (5) Elovichmentioning
confidence: 91%
“…It is important to note that arsenic (As) is a metalloid and selenium (Se) is a nonmetal, however, the term "heavy metal" will be used for the description of the elements studied in this paper. Although trace concentration of some of these elements (Fe, Cu, Cr, Zn, Se, Mn, Ni) are vital for some biochemical processes and physiological functions, they can persist in the environment and can cause serious health problems even at low concentrations (Ali et al, 2016;Amuda et al, 2007;Aremu et al, 2002;Chowdhury et al, 2016;Gautam et al, 2014;Karadag, 2008;Koubaissy et al, 2014;Li et al, 2017;Sencan et al, 2015;Wan Ngah and Hanafiah, 2008;Wang and Chen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several processes such as coagulation/flocculation, oxidation/precipitation, adsorption/biosorption, electrochemical processes, ion-exchange, bioremediation, floatation, evaporation, photocatalysis and membrane technology can be used for the removal of heavy metals (Barakat, 2011;Bestawy et al, 2012;Blöcher et al, 2003;Gunatilake, 2015;Wahyuni et al, 2015). Among these methods, adsorption/biosorption is one of the preferred methods due to its easy application, cost effectiveness, high efficiency, regeneration capacity, easy recovery and sludge-free operation (Amuda et al, 2007;Aremu et al, 2002;Gautam et al, 2014;Kadirvelu et al, 2001;Karadag, 2008;Koubaissy et al, 2014;Vaghetti et al, 2009;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wernert et al (2005) mentioned the use of activated carbon as adsorbent for different uremic toxins. Activated carbon is characterized by its highly developed porosity, large surface area, variable characteristics of surface chemistry, and high degree of surface reactivity (Koubaissy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%